FC 027COVID-19 IN PATIENTS ON KIDNEY REPLACEMENT THERAPY - CLINICAL CHARACTERISTICS AT TRIAGE ASSOCIATED WITH ADMISSION, READMISSION AND SHORT-TERM OUTCOMES. (29th May 2021) - Mitra, Sandip; Jayanti, Anu; Vart, Priya; Coca, Armando; Gallieni, Maurizio; Altern Øvrehus, Marius; Midtvedt, Karsten; Abd ElHafeez, Samar; Gandolfini, Ilaria; Büttner, Stefan; Franssen, Casper; Hemmelder, Marc
Abstract: Background and Aims: Patients on kidney replacement therapy (KRT) are at high risk of developing severe COVID-19 illness and often require high intensity care and utilisation of hospital resources. During the ongoing pandemic, the optimal care pathway and triage for KRT patients presenting with varying severity of COVID-19 illness is unknown. We studied clinical factors and outcomes associated with admission, readmission and short-term outcomes. Method: Data from the European Renal Association COVID-19 Database (ERACODA) was analysed. This database includes granular data on dialysis patients and kidney transplant recipients with COVID-19 from all over Europe. The clinical and laboratory features at first presentation of hospitalized and non-hospitalized patients and those who returned for second presentation were studied. In addition, possible predictors of outcome in those who were not hospitalized at first presentation were identified. Results: Among 1, 423 KRT patients (haemodialysis; 1017/kidney transplant; 406) with COVID-19, 25% (n=355) were not hospitalized at first presentation. Of them, only 10% (n=36), presented for a second time in the hospital. The median interval between the first and second presentation was 5 days (Interquartile interval: 2-7 days). Patients who re-presented had worsening of pulmonary symptoms, a fall in oxygen saturation (97% to 90%), and an increase in C-reactive protein (26 mg/L to 73 mg/L) between their attendances. Patients who re-presented after initial assessment were older (72 vs. 63 years) and initially more often had pulmonary symptoms and abnormalities on lung imaging compared with those who did not present for a second time. The 28-day mortality rate of patients admitted at the second presentation was similar to that of patients admitted at first presentation (26.5% vs. 29.7%, p=0. 61). Among patients who were not hospitalized at first presentation (mortality 6%), age, prior smoking, clinical frailty scale, and shortness of breath at first presentation were identified as predictors of mortality. Conclusion: KRT patients with COVID-19 and mild pulmonary abnormalities and no signs of pulmonary insufficiency can be safely returned without hospitalization. These patients should be advised to seek immediate contact when they develop respiratory distress. Our findings provide support for a risk-stratified clinical approach to admissions of KRT patients presenting with COVID-19. The study findings may be valuable for clinical triage and optimising hospital capacity utilisation during the ongoing pandemic.